2024
DOI: 10.32859/era.28.9.1-29
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal appraisal of the medicinal flora among the sub-alpine and alpine Iindigenous communities of Palas Valley Kohistan, Northern Pakistan

Sadaf Kayani,
Mushtaq Ahmad,
Syed Waseem Gillani
et al.

Abstract: Background:The contemporary research was conducted to explore the ethnomedicinal potential of wild flora exploited by the indigenous communities of Palas valley of Kohistan, Northern Pakistan. It constitutes an important contribution to the knowledge of biological resources used for treatment of ailments through traditional practices.Methods: Rapid appraisal approach (RAA), semi-structured interviews, and personal monitoring, group discussion with community and interviews with herbalist were carried out to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The results reveal that leaves are the most utilized plant part, accounting for approximately 46.05% (35 citations), followed by aerial parts at 15.79% (12 citations). Additionally, seeds, flowers, fruits, and roots are used at rates of 14.47%, 14.47%, 11.84%, and 10.53%, respectively (11,11,9, and 8 citations, respectively) (Fig. 6A).…”
Section: Used Parts Plant State Mode Of Preparation and Administratio...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results reveal that leaves are the most utilized plant part, accounting for approximately 46.05% (35 citations), followed by aerial parts at 15.79% (12 citations). Additionally, seeds, flowers, fruits, and roots are used at rates of 14.47%, 14.47%, 11.84%, and 10.53%, respectively (11,11,9, and 8 citations, respectively) (Fig. 6A).…”
Section: Used Parts Plant State Mode Of Preparation and Administratio...mentioning
confidence: 99%
“…According to the World Health Organization (WHO), phytotherapy is the most widely used medical treatment worldwide (6). In developing countries, the utilization of plants as medicines constitutes a significant component of the healthcare system (7)(8)(9)(10). Ishtiaq and Khan (11) reported that over 80% of prescribed medicines originate from substances extracted from medicinal plants or are developed using semi-synthetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have functioned as a natural reservoir for remedies and therapies, from ancient times, medicinal herbs have gained popularity due to their broad use and fewer side effects. The globe has seen a surge in plant research in recent years, and a wealth of data has been gathered to demonstrate the enormous potential of medicinal plants utilized in a variety of traditional systems (1)(2)(3). Indian medicinal plants are considered a vast source of several pharmacologically active principles and compounds, which are frequently utilized in home remedies against a variety of illnesses (4).…”
Section: Introductionmentioning
confidence: 99%
“…The southern region is rich ethnically, ecologically and topographically. The local people use traditional medicine to cope with day-to-day illnesses (Kayani et al 2024. In spite of this, areas of southern lowlands are still overlooked.…”
Section: Introductionmentioning
confidence: 99%